Book Selection and the Five Laws - Languidge, D. W. (Journal of Information and Knowledge, 1968)
Reviews S R Ranganathan's Library book selection Ed 2 (1966). Points out that the derivation and explicit statements of the principles of book selection on the basis of the Five Laws of Library Science - formulated in 1928 and published in 1931-conforms to the scientific method and that they are helpful. Deals with in some detail about certain controversies in book selection censorship and the question of quality demand. Remarks about the helpfulness of the structuring of the text in preserving unity of idea in each of its structural elements. A parallel is drawn between the need for co-operation in book selection and in document retrieval. Points out that most of the principles of book selection enumerated in the book are valid in different kinds of libraries the world over.